2014
DOI: 10.1021/nn505051d
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying the Red-Emission of Upconverting Nanoparticles for Biocompatible Clinically Used Prodrug-Induced Photodynamic Therapy

Abstract: A class of biocompatible upconverting nanoparticles (UCNPs) with largely amplified red-emissions was developed. The optimal UCNP shows a high absolute upconversion quantum yield of 3.2% in red-emission, which is 15-fold stronger than the known optimal β-phase core/shell UCNPs. When conjugated to aminolevulinic acid, a clinically used photodynamic therapy (PDT) prodrug, significant PDT effect in tumor was demonstrated in a deep-tissue (>1.2 cm) setting in vivo at a biocompatible laser power density. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
190
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(198 citation statements)
references
References 47 publications
(76 reference statements)
2
190
0
2
Order By: Relevance
“…Recently, CaF 2 shell has emerged as a great candidate to replace the commonly used NaYF 4 shell due to its optical transparency, biocompatibility, stability, high crystallizability and negligible lattice mismatch with NaYF 4 155, 156, 157, 158, 159. For example, Wang et al demonstrated a facile way to fabricate NaYF 4 :Ln 3+ @CaF 2 nanocrystals with ≈300‐fold enhancement of upconverted emission yield compared with the parent core NaYF 4: Ln 3+ .…”
Section: Effects Of Nir Light Power Intensity On the Upconverting Phementioning
confidence: 99%
“…Recently, CaF 2 shell has emerged as a great candidate to replace the commonly used NaYF 4 shell due to its optical transparency, biocompatibility, stability, high crystallizability and negligible lattice mismatch with NaYF 4 155, 156, 157, 158, 159. For example, Wang et al demonstrated a facile way to fabricate NaYF 4 :Ln 3+ @CaF 2 nanocrystals with ≈300‐fold enhancement of upconverted emission yield compared with the parent core NaYF 4: Ln 3+ .…”
Section: Effects Of Nir Light Power Intensity On the Upconverting Phementioning
confidence: 99%
“…Therefore, UCNPs have many advantages in imaging such as minimal autofluorescence background signals and high resistance to photobleaching, which make them suitable for sensitive detection and imaging in complicated biological samples. [24][25][26] In our previous studies, ultra-sensitive in vivo stem cell tracking with a detection limit down to as few as ten cells in a mouse have been realized by labeling cells with UCNPs. 27,28 Therefore, we hypothesize that engineered UCNPs loaded with antigens may be used to label and stimulate DCs, which after being administrated into animals could be tracked by in vivo UCL imaging and finally realize DC-based immunotherapy with high efficiency.…”
mentioning
confidence: 99%
“…[42][43][44] A class of biocompatible UCNPs with largely ampli¯ed red-emissions were also developed by Han's group. 45 The quantum yield of red emission reached 3.2, which is 15-fold stronger than the known -phase core/shell UCNPs. And the redemission of UCNPs could penetrate a deep-tissue (>1.2 cm) setting in vivo at a harmless laser power density.…”
Section: Thermal Decomposition Methodsmentioning
confidence: 90%